A latent profile analysis of sleep disturbance in relation to mental health among college students in China - Chen, Chunping; He, Zigeng; Xu, Bingna; Shao, Jianyao; Wang, Dongfang (Frontiers in Public Health, 2023)
Aims: This study aimed to examine the subtype classification characteristics of sleep disturbance (SD) in college students and their associations with sample characteristic factors and mental health outcomes. Methods: The sample comprised 4302 college students (Mean age = 19.92 ± 1.42 years, 58.6% females). The Youth Self Rating Insomnia Scale, 21-item Beck Depression Inventory, 8-item Positive Subscale of the Community Assessment of Psychic Experiences, 10-item Connor-Davidson Resilience Scale were used to assess adolescents’ sleep disturbance, depressive symptoms, psychotic-like experiences (PLEs) and depressive symptoms, and resilience. Latent profile analysis, logistic regression and liner regression analysis were used to analyze the data. Results: Three subtypes of SD in college students were identified: the severe SD profile (10.6%), the moderate SD profile (37.5%), and the low SD profile (51.9%). Compared with college students in the “low SD” profile, risk factors for “severe SD” include being male and poor parental marital status. Sophomores were found to predict the “severe SD” profile or “moderate SD” profile relative to the “low SD” profile. College students in the “moderate SD” profile or “severe SD” profile were more likely to have a higher level of depressive symptoms and PLEs, while a lower level of resilience. Conclusion: The findings highlighted that target intervention is urgently needed for male college students, sophomores and those with poor parental marital status in the “moderate SD” profile or “severe SD” profile.